Absolute temperature measurements by direct-frequency-comb spectroscopy. (November 2020) - Galzerano, Gianluca
Highlights: Doppler Broadening Thermometry with a direct-frequency-comb spectroscopy method. Simultaneous measurement of 28 acetylene absorption lines at around 1.54 μm. Room temperature measurements with an uncertainty of 190 mK over 15 s. Uncertainty budget analysis and experimental strategies to reach mK accuracy. Abstract: The absolute temperature of acetylene gas is measured by an effective yet simple implementation of Doppler-broadening thermometry. At room temperature the combined measurement uncertainty is ∼ 200 mK over 15 s measurement time. A large set of 28 lines in the near infrared region from 1.537 to 1.540 μ m, belonging to the P branch of the ν 1 + ν 3 rovibrational band of 12 C2 H2 and 13 C 12 CH2 at low pressure, has been addressed using for the first time a direct frequency-comb spectroscopic approach to retrieve the Doppler linewidths and hence the thermodynamic gas temperature. Experimental strategies to reach the millikelvin accuracy level are discussed.